2004
DOI: 10.2337/diacare.27.11.2610
|View full text |Cite
|
Sign up to set email alerts
|

The Blood Glucose Monitoring Communication Questionnaire

Abstract: OBJECTIVE -The aim of this study was to present the psychometric properties of a new tool for evaluating affective response to blood glucose monitoring (BGM) in youths with type 1 diabetes and their parents. RESULTS -Youth and parent BGMC questionnaires had acceptable internal consistency (youth, ␣ ϭ 0.77; parent, ␣ ϭ 0.82) and 1-year test-retest reliability (youth, r ϭ 0.60; parent, r ϭ 0.80). Higher BGMC questionnaire scores (indicating more negative affect) showed a strong association with higher levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 21 publications
0
42
1
3
Order By: Relevance
“…Studies have consistently found that high family conflict is related to poorer diabetes self-care behaviors and poorer metabolic control, while positive family attributes such as support, warmth, and cohesion are associated with better diabetes self-care behaviors and metabolic control (31,33,108 -110). Data from several studies indicate that parental (predominantly maternal) psychological wellbeing correlates positively with all diabetes metabolic outcomes in their children (i.e., happier mother and better outcomes) (111,112). This finding is similar to a study of patient-perceived family stress in adults by Parkerson et al (113) but is at odds with a more recent study of diabetes-related stress by Stallwood (114).…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…Studies have consistently found that high family conflict is related to poorer diabetes self-care behaviors and poorer metabolic control, while positive family attributes such as support, warmth, and cohesion are associated with better diabetes self-care behaviors and metabolic control (31,33,108 -110). Data from several studies indicate that parental (predominantly maternal) psychological wellbeing correlates positively with all diabetes metabolic outcomes in their children (i.e., happier mother and better outcomes) (111,112). This finding is similar to a study of patient-perceived family stress in adults by Parkerson et al (113) but is at odds with a more recent study of diabetes-related stress by Stallwood (114).…”
contrasting
confidence: 55%
“…The mediating variable between caregiver stress and diabetes outcomes may be the circumstances around blood glucose monitoring (BGM). Disagreement about responsibility of BGM and the level of affect surrounding BGM have both been found to be associated with metabolic outcome (112).…”
mentioning
confidence: 99%
“…Total scores can range from a minimum of 8 (indicating no negative affect) to 24 (indicating a high level of negative affect). This survey shows strong psychometric properties with regard to internal consistency and predictive validity (19). It can be completed in Ͻ5 min.…”
Section: Dfcsmentioning
confidence: 99%
“…Blood Glucose Monitoring Communication Questionnaire. The Blood Glucose Monitoring Communication (BGMC) questionnaire was designed to evaluate emotional responses to BGM results experienced by youth and their caregivers (19). Youth and their caregivers were asked to report their emotional responses to high and low blood glucose levels.…”
Section: Dfcsmentioning
confidence: 99%
“…Diabetes-specific constructs such as fear of hypoglycemia and hyperglycemia, as well as tendency to have negative emotional reactions to glucose readings, will also likely influence use of diabetes technology. 67,68 Numerous studies support the relationship between the HBM and a wide range of diabetes self-care behaviors in both adolescents and adults, including foot care 69 and adherence to insulin, diet, and exercise. [70][71][72][73] The TPB is another behavior change model that predicts diabetes management behaviors, including a healthy diet and engaging in physical activity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%